Leveraging Digital Transformation for Family-Owned Small Businesses Refinement: A Case Study of a Boutique Hotel - Mihaela GOLOGAN; Florina ATANASE (MURAR) (Communications of International Proceedings, 2025)
Digital transformation is a must for business to maintain their market share. Many researchers are concentrated on medium and large companies. They are the first adopters, being able to strike the financial barriers. Meanwhile, among small businesses exists a trepidation between the need and fear of change. The advantages of digitalization are acknowledged, but the results appear after many years of struggling to overcome obstacles. How can small businesses, particularly family businesses, push their limits and afford to work towards digitalization? Analysing a case study of a small family business owning a boutique hotel, it is confirmed that dedicated engagement to change on long-term generated performance business results. A step-by-step approach, it allows business owners to combine self-adjustment with people engagement to adopt digitalization, balancing the financial resources needed during the process. This research proves that the widely spread panic to change is an obstacle that any company can manage, no matter their dimension and existing resources. Meanwhile, exploring this case study is a benchmark opportunity for researchers and businesses contributing to the increasingly demanding world to have personalised and unique services.
Keywords: Digitalization; Small Business; Hospitality; digital transformation